Targeted Next-Generation Sequencing in Pneumonia: Applications in the Detection of Responsible Pathogens, Antimicrobial Resistance, and Virulence - Liu B; Bao Z; Chen W; Xi X; Ge X; Zhou J; Zheng X; Zhang P; Deng W; Ding R; Zhou M; Fang J (Infection and Drug Resistance)
Bing Liu,1– 3,* Zhiyao Bao,1– 3,* Wei Chen,1– 3,* Xiaotong Xi,4,5,* Xiao Ge,1– 3 Jun Zhou,1– 3 Xiaoyan Zheng,6 Peipei Zhang,4,5 Wanglong Deng,4,5 Ran Ding,4,5 Min Zhou,1– 3 Jie Fang7 1Department of Pulmonary and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China; 2Institute of Respiratory Diseases, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China; 3Shanghai Key Laboratory of Emergency Prevention, Diagnosis and Treatment of Respiratory Infectious Diseases, Shanghai, 200025, People’s Republic of China; 4State Key Laboratory of Neurology and Oncology Drug Development, Jiangsu Simcere Diagnostics Co., Ltd., Nanjing Simcere Medical Laboratory Science Co., Ltd., Nanjing, 210018, People’s Republic of China; 5Nanjing Simcere Medical Laboratory Science Co., Ltd., Nanjing, 210018, People’s Republic of China; 6Department of Pulmonary and Critical Care Medicine, Zhoushan Branch of Ruijin Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Zhoushan, 316000, People’s Republic of China; 7Department of Pharmacy, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Fang, Department of Pharmacy, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, No. 197, Rui Jin 2nd Road, Shanghai, 200025, People’s Republic of China, Email fj40517@rjh.com.cn Min Zhou, Department of Pulmonary and Critical Care Medicine, Ruijin Hospital, Shanghai Jiao Tong University School of Medicine, No. 197, Rui Jin 2nd Road, Shanghai, 200025, People’s Republic of China, Email doctor_zhou_99@163.comBackground: Targeted next-generation sequencing (tNGS) is a high-throughput and cost-effective diagnostic alternative for pneumonia, with the ability to simultaneously detect pathogens, antimicrobial resistance genes, and virulence genes. We aimed to explore the applicability of tNGS in the co-detection of the responsible pathogens, antimicrobial resistance (AMR) genes, and virulence genes in patients with pneumonia.Methods: A prospective study was conducted among patients with suspected pneumonia at Ruijin Hospital from March 1 to May 31, 2023. Bronchoalveolar lavage fluid (BALF) or sputum samples were collected and sent for tNGS, metagenomic next-generation sequencing (mNGS), and conventional microbiological tests (CMTs).Results: In total, 67 BALF and 11 sputum samples from 78 patients were included in the analyses. According to the composite reference standards, the accuracy of tNGS in the detection of responsible pathogens was 0.852 (95% confidence interval 0.786– 0.918), which resembled that of mNGS and remarkably exceeded that of CMTs. In addition, 81 AMR genes associated with responsible pathogens were reported, and 75.8% (25/33) priority drug-resistant pathogens could be directly identified. A total of 144 virulence genes were detected for four common pathogens. And patients with virulence genes detected were of higher proportions of severe pneumonia (95.0% vs 42.9%, P = 0.009), acute respiratory distress syndrome (55.0% vs 0%, P = 0.022), and neutrophils (82.3% vs 62.2%, P = 0.026) than those not.Conclusion: In patients with pneumonia, tNGS could detect the responsible pathogens, AMR genes, and virulence genes simultaneously, serving as an efficient and cost-effective tool for the diagnosis, treatment, and severity indication of pneumonia.Keywords: targeted next-generation sequencing, pneumonia, pathogen, antimicrobial resistance, virulence